Analysis of physician characteristics and factors influencing the online recommendation of pediatric orthopaedic surgeons: a cross-sectional study. Issue 6 (6th November 2022) - Pando, Alejandro; Delprete, Cristina R.; Su, Jennifer; Edobor-Osula, Folorunsho
Abstract : Background: Physician online reviews are a growing resource that patients use to choose healthcare providers. The authors investigated the factors involved in the recommendation of pediatric orthopaedic surgeons on a popular online physician-rating website. Methods: A cross-sectional study was conducted using the 2020-2021 Pediatric Orthopedic Society of North America directory to identify United States active board-certified pediatric orthopaedic surgeons. Healthgrades.com was used to gather data including geographic location, years of experience, type of ratings, age, sex, and likelihood to recommend score (LTRS). Quantitative analysis was conducted using descriptive statistics, Student t -test, Analysis of Variance (ANOVA), Pearson correlation, and multiple linear regression models. Results: Seven hundred and one POSNA members (566 men, 135 women) were identified. A higher likelihood to recommend score (LTRS) was associated with short waiting times ( P <0.0001), reports of "appointment not being rushed" ( P =0.001), and more total ratings ( P =0.130). Male physicians were positively associated with LTRS ( P =0.01). Surgeons with fewer years of experience had fewer negative reviews ( P =0.02) and were more favorably rated ( P <0.05). Patients gave more positive (mean=3.37) then negative (mean=0.73) reviews and selected more "what went well" factors (mean=72) rather than "what could be improved" factors (mean=13). The South had more total, positive, and 5-star ratings ( P <0.01). Conclusions: Patients are more likely to rate pediatric orthopaedic surgeons on the two extremes when using online reviews. Physicians with the fewer years practicing received higher LTRS, suggesting satisfaction is not related to experience. Factors such as reducing waiting times and not rushing appointments may help improve the likelihood of physicians being recommended in the future. Level of Evidence: Level IV.